2021
DOI: 10.1016/j.biomaterials.2020.120611
|View full text |Cite
|
Sign up to set email alerts
|

3D culture of HepaRG cells in GelMa and its application to bioprinting of a multicellular hepatic model

Abstract: Bioprinting is an emergent technology that has already demonstrated the capacity to create complex and/or vascularized multicellular structures with defined and organized architectures, in a reproducible and high throughput way. Here, we present the implementation of a complex liver model by the development of a three-dimensional extrusion bioprinting process, including parameters for matrix polymerization of methacrylated gelatin, using two hepatic cell lines, Huh7 and HepaRG. The printed structures exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 62 publications
3
94
1
1
Order By: Relevance
“…Albumin synthesis was elevated at day 6 of spheroid culture, and mRNA levels of CYP1A2 , CYP2B6 and CYP3A4 first dropped, then slightly increased at day 4 and were elevated 1.2–3 -fold at day 7 when compared to day 0 [ 77 ]. Additionally, others have shown that HepaRG spheroids (self-aggregated or bioprinted) could be cultured over several weeks and that those cultures maintained several hepatic properties: HepaRG spheroids were capable of (a) albumin [ 87 , 88 , 89 , 90 , 91 ] and urea [ 87 , 90 ] production, (b) displayed expression and activity of CYP1A2 [ 88 , 89 ], CYP2B6 [ 89 ] and CYP3A4 [ 86 , 88 , 89 , 90 , 92 ], (c) showed phase II enzyme activity [ 89 , 91 ], and (d) displayed cellular polarization shown by MRP2 [ 87 , 88 , 90 ] and Pgp [ 91 ] expression, and by F-actin bands, indicative of bile canalicular structures [ 89 , 91 , 92 ]. Regarding expression and activity of phase I enzymes, however, several studies have shown that basal levels in spheroids were unaffected, in part even slightly lower than in monolayer cultures.…”
Section: Three-dimensional Culture Models For Human Hepatocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Albumin synthesis was elevated at day 6 of spheroid culture, and mRNA levels of CYP1A2 , CYP2B6 and CYP3A4 first dropped, then slightly increased at day 4 and were elevated 1.2–3 -fold at day 7 when compared to day 0 [ 77 ]. Additionally, others have shown that HepaRG spheroids (self-aggregated or bioprinted) could be cultured over several weeks and that those cultures maintained several hepatic properties: HepaRG spheroids were capable of (a) albumin [ 87 , 88 , 89 , 90 , 91 ] and urea [ 87 , 90 ] production, (b) displayed expression and activity of CYP1A2 [ 88 , 89 ], CYP2B6 [ 89 ] and CYP3A4 [ 86 , 88 , 89 , 90 , 92 ], (c) showed phase II enzyme activity [ 89 , 91 ], and (d) displayed cellular polarization shown by MRP2 [ 87 , 88 , 90 ] and Pgp [ 91 ] expression, and by F-actin bands, indicative of bile canalicular structures [ 89 , 91 , 92 ]. Regarding expression and activity of phase I enzymes, however, several studies have shown that basal levels in spheroids were unaffected, in part even slightly lower than in monolayer cultures.…”
Section: Three-dimensional Culture Models For Human Hepatocytesmentioning
confidence: 99%
“…This might be explained by the relatively high basal expression of several CYP enzymes in HepaRG cells. However, the authors of those studies have deemed it necessary to elevate expression and activity of CYPs by induction using β-naphthoflavone (for CYP1A2), phenobarbital (for CYP2B6) or rifampicin (for CYP2C9 and CYP3A4) to reach more relevant levels [ 87 , 89 , 91 , 93 ].…”
Section: Three-dimensional Culture Models For Human Hepatocytesmentioning
confidence: 99%
“…Drug hepatotoxicity testing showed increased sensitivity to APAP compared to 2D adhesion controls. In addition, 3D extrusion bioprinting was used to fabricate a complex liver model [106]. The bioprinted structure showed 28-day cell viability and liver function.…”
Section: D-printed Liversmentioning
confidence: 99%
“…GelMA maintains high cellular viability with high shape integrity post-printing making it an excellent bioink for larger tissue constructs ( Figure 2 H) [ 69 ]. It has been extensively used in the bioprinting community to create a multitude of constructs, including skin, cartilage, tumors, cornea, blood vessels, and liver and cardiac tissues, capitalizing on the strong bioink–cell interactions and resulting in a bioink that can be used for a wide number of tissues [ 43 , 76 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ].…”
Section: Biological Bioinksmentioning
confidence: 99%